Effect of Hemodialysis Duration on Left Ventricular Hypertrophy in Patients of Chronic Kidney Disease - Shabahat Ali, Rana Muhammad Umar, Bilal Ahmed, Faryad Ali, Qazi Abdul Saboor, Furqan Yaqub Pannu (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To ascertain the effect of duration of hemodialysis on left ventricular hypertrophy in patients with chronic kidney disease. Design: It was a cross sectional observational study. Study Settings: Department of Cardiology, Shaikh Zayed Hospital Lahore over a period of 6 months from January 2021 to June 2021. Material and Methods: This study was conducted, between February and September 2021, by recruiting 200 patients undergoing hemodialysis. Demographic and clinical data were recorded. Blood samples were taken for investigation. Body surface area was calculated using Du Bois Formula. To calculate LVM, Echocardiography (Echo) was done by using 2D M-mode in the standard manner. At the end of data collection, data was entered and analyzed using SPSS v.21. Single and multiple linear regression analysis were used to calculate impact of duration and other confounding variable on LVM. Results: The mean age of the participants was 46.77±13.263. About 58.5% (117) were males and 41.5% (83) were females. Prevalence of LVH was 171(85.5%). The mean LVM for males and females was 248.44±26.67g and 182.88±22.43g respectively. Most of the participants (47.0%) were receiving HD for 25-36 months followed by 26.0%, 15.0%, 12.0% for 13-24 months, 3-12 months,37-48 months respectively. LVH was found to be strongly positively correlated with duration of dialysis. Increasing duration of HD was associated with an increased likelihood of exhibiting LVH. Conclusion: The study concluded that there exist significantly strong relationship between increased duration of hemodialysis in CKD patients with frequency of left ventricular hypertrophy. So, in future practice it is recommended to focus on CKD patients undergoing hemodialysis with regard to duration of hemodialysis and expected frequency of left ventricular hypertrophy and its timely management. Keywords: Chronic kidney disease, Left ventricular hypertrophy, Left ventricular mass index, Haemodialysis.